Prolonged survival of patients with peripheral T-cell lymphoma after first-line intensive sequential chemotherapy with autologous stem cell transplantation - Procházka, Vít; Faber, Edgar; Raida, Luděk; Vondráková, Jana; Kučerová, Ladislava; Jarošová, Marie; Indrák, Karel; Papajík, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2009)
BACKGROUND: Nodal peripheral T-cell lymphomas (PTCLs) are infrequent subtypes of non-Hodgkin's lymphomas. The WHO classification recognizes three subgroups of nodal PTCL: peripheral T-cell lymphoma not otherwise specified (PTCL, NOS), anaplastic large cell lymphoma (ALCL) and angioimmunoblastic lymphoma (AIL). The clinical course is aggressive and despite multiagent chemotherapy, the median survival is about 2 years. Optimal first-line chemotherapy is not established and the role of high-dose therapy with autologous stem cell support is still controversial. AIM: To analyze the long-term outcome of PTCL patients treated with intensive first-line chemotherapy with highdose therapy and autologous transplant consolidation. METHOD: Sequential chemotherapy protocol consisting of 3 cycles of CHOEP-21-like regimen (PACEBO), 1 cycle of an ifosfamide and methotrexate-based regimen (IVAM) and a priming regimen with high-dose cytosine arabinoside (HAM). Consolidation was provided with myeloablative conditioning (BEAM 200) and autologous stem cell support. Eighty-four patients with aggressive high-risk lymphoma were treated with the sequential protocol from 2000 to 2007 in our institution. Here we report our experience with 18 patients with nodal PTCL (10 PTCL, NOS; 3 ALCL, ALKnegative; 2 ALCL, ALK-positive; 2 ALCL, unknown ALK status; 1 AIL). RESULTS: Eleven (61 %) patients achieved complete remission, 3 (17 %) partial remission and 4 (22 %) patients failed the procedure. The overall response rate was 77.8 %. After a median follow-up of 25.7 months, nine patients relapsed or progressed (6 PTCL, NOS; 2 ALCL ALK-positive; 1 ALCL ALK-negative; median 14.1 months) and four patients died (lymphoma progression). The relapse was treated with allogeneic stem transplantation in one patient. The 2-year progression-free survival (PFS) was 52 % (95 % CI, 0.27 to 0.76); the 2-year overall survival rate reached 71 % (95 % CI, 0.47 to 0.95). CONCLUSION: Our results show that intensive first-line chemotherapy with high-dose therapy and autologous transplant consolidation offers a chance for long-term survival in patients with chemosensitive PTCL.
Keywords: financování organizované; dospělí; Female; kombinovaná terapie; Adult; periferní T-buněčný lymfom; ženské pohlaví; přežití bez známek nemoci; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; míra přežití; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Financing, Organized; Male; Combined Modality Therapy; Aged; Lymphoma, T-Cell, Peripheral; Transplantation, Homologous; Survival Rate; Disease-Free Survival; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans